Compounds identified on hexane and dichloromethane extracts of Salicornia ramosissima - Isca, Vera M. S. (2012)
Salicornia ramosissima J. Woods (common purple glasswort) is an annual halophyte, widely distributed in the salt marsh of Ria de Aveiro (Portugal), that belongs to the Salicornia L. genus (Chenopodiaceae).[4] Although phytochemical studies genus on this genus report the presence of compounds which are well-recognized for their biological activities, such as flavonoids, chromones and alkaloids,[3] too little is known about secondary metabolites on purple glasswort. In our previous work we were able to isolate and identify ethyl o-hydroxycinnamate, (E)-fatty alcohol ferulic acid and scopoletin from the dichloromethane extract of S. ramosissima aerial parts. The structure and spectroscopic characterization of some secondary metabolites isolated from dichloromethane crude extract also will be presented and discussed.